Associated factors to the sexual behavior in Peruvian women among 15 and 25 years old - Arias Gallegos, Walter L (2021)
Background: The sexual behavior of women is associated with various protective or risk factors, which are important to assess. To determine the socioeconomic factors associated with the sexual behavior of Peruvian women within 15 and 25 years old. Method: A secondary analysis of the 2016 Demographic and Family Health Survey (ENDES) was conducted. Our sample was 7962 women from 15 to 25 years old, from all over the Peruvian territory. Associative analyzes were carried out on the age of sexual initiation, the number of sexual partners and the use of contraceptives, based on sociodemographic variables. Poisson regression with robust variance was also used. Results: It was found the factors, that are associated with the age of sexual initiation and the number of sexual partners, are the area of origin, marital status, educational level, employment status and socioeconomic level. While women who work and whose partners do not drink alcohol are the most likely to use contraceptives. Conclusions: It can be concluded that certain socioeconomic and work conditions act as protective factors of female sexual behavior, while having a partner who drinks alcohol is a risk factor.